FIBRO DYSPLASIA OSSIFICANS PROGRESSIVA - Ahmed, Waqas; Safdar, Aqeel; Ahmed, Iftikhar; Ahmed, Naveed (Journal of Ayub Medical College Abbottabad, 2018)
We present a case of a 7 years old boy with a very rare debilitating autosomal dominant disorder characterized by heterotopic ossification. Fibro dysplasia ossificans progressiva affects 1 in 2 million individuals with only 2 previous cases reported from this region. The disease manifests as multiple foci of bone formation in muscles, fasciae, tendons and ligaments often triggered by trauma. The child was born with bilateral short hallux valgus and aplasia of distal phalanges of both thumbs. In the last 3 years he had developed hard bony swellings in the scalp, followed by limitation of neck mobility. He developed palpable nodules on the right lateral thoracic cage over the last 1 year following trauma. Heterotopic bone formation was also seen in both tibias. FOP causes irreversible lesions of ossification thus early institution of prophylactic measures, counselling regarding avoidance of trauma and surgery can significantly reduce acute exacerbations of this rare disease. Keywords: Fibro dysplasia ossificans progressive; Heterotopic ossification; Hallux valgus